On the categories of L-Valued and Q-Valued 6 deterministic fuzzy automata - Dubey, M. K.; Tiwari, S. P.; Kavikumar, J. (World Scientific Publishing Co., 2021)
Automata and languages have been studied in the context of different lattice structures by several authors. This paper is toward the categorical study of deterministic lattice-valued (L-valued) fuzzy automata and deterministic quantale-valued (Q-valued) fuzzy automata. The existence of initial and final objects in the subcategory of category of deterministic lattice-valued fuzzy automata is shown. We also show that there is an adjunction between the category of deterministic lattice-valued and quantale-valued fuzzy automata.